Constructing Cause in International Relations / [electronic resource] - Lebow, Richard Ned (Cambridge : Cambridge University Press, 2014)
Cause is a problematic concept in social science, as in all fields of knowledge. We organise information in terms of cause and effect to impose order on the world, but this can impede a more sophisticated understanding. In his latest book, Richard Ned Lebow reviews understandings of cause in physics and philosophy and concludes that no formulation is logically defensible and universal in its coverage. This is because cause is not a feature of the world but a cognitive shorthand we use to make sense of it. In practice, causal inference is always rhetorical and must accordingly be judged on grounds of practicality. Lebow offers a new approach - 'inefficient causation' - that is constructivist in its emphasis on the reasons people have for acting as they do, but turns to other approaches to understand the aggregation of their behaviour. This novel approach builds on general understandings and idiosyncratic features of context.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: International relations; Social sciences and state